Morphometric analysis of Nandakini River Basin, Garhwal Himalaya, Uttarakhand using geospatial technology - Patra, Gopinath; Mukherjee, Sucheta; Jha, Vibhash C. (National Geographical Journal of India, 2022)
Basin morphometry is a crucial method of analysis to understand the geology, lithological structure, inltration rate of rainwater, runoff, eroded load carrying capacity and ooding potential of a drainage basin. The quantitative techniques applied for linear, areal and relief aspects of the drainage basin elucidate the rate of erosion, the intensity of denudation and subsequently the potential of the Nandakini river basin to ooding. The morphometric analysis of the Nandakini river basin in the Garwhal Himalayan region of Uttarakhand reveals that the Rf value of the Nandakini river basin is 0.28, indicating an elongated basin shape leading to quick ooding and poor draining out of oodwaters. Similarly, an elevation difference between the highest and lowest elevation is 5380 which metres aids quick runoff and deposition of eroded debris in the drainage channels, another cause of channel overow. The Rh value is high (0.12), indicating a high channel gradient with intense erosional processes operating due to steep gradient and this has a considerable impact on the rate of erosive geomorphic processes operating. The higher elevation on the Eastern part of the basin due to the Vaikrita Thrust, the Munsiyari Thrust (ie. the southern tilting Main Central Thrust) and the Baijnath Klippe has resulted in metamorphism in Miocene and Pliocene explaining the low rate of inltration and rapid runoff.